Using Debate in an Online Asynchronous Social Policy Course - Mitchell, Elissa Thomann (Online Learning, 2019)
This paper presents the use of a debate in an online asynchronous social policy course. Debate is frequently used as an instructional strategy in higher education, but little is known about the use of this tool in an online learning environment. Participants (N = 36) completed an online debate assignment and both qualitative (reflection papers) and quantitative (survey) data was gathered to learn about the effectiveness of the assignment, and what students learned, liked, and disliked about the project. A majority of students reported the debate assignment helped them further understand course concepts, understand concepts better than lecture or reading would have, use or improve critical thinking skills, and improve collaboration among students in the course. Key themes from qualitative data are also reported, as well as recommendations for using this assignment in other courses.